How Chemometrics Revives the UV-Vis Spectroscopy Applications as an Analytical Sensor for Spectralprint (Nontargeted) Analysis - Ríos Reina, Rocío (2023)
In recent years, methodologies based on spectral analysis, using ultraviolet–visible (UV-Vis) radiation, have experienced an amazing development and have been widely applied in various fields such as agricultural, food, pharmaceutical, and environmental sciences. This straightforward technique has re-emerged with novel and challenging proposals to solve, in a direct and fast way, a wide variety of problems. These reaches would not have been possible without the essential support of chemometrics. In this sense, under the general background of the development in data and computer science, and other technologies, the emergence of innovative ideas, approaches, and strategies endows UV-Vis spectroscopy with a new vitality as an analytical sensor with the capability of significantly improving both the robustness and accuracy of results. This review presents modern UV-Vis spectral analysis, which is on the rise, associated with comprehensive chemometric methods that have become known in the last six years, especially from the perspective of practicability, including spectral preprocessing, wavelength (variable) selection, data dimension reduction, quantitative calibration, pattern recognition, and multispectral data fusion. Most importantly, it will foresee future trends of UV-Vis spectroscopy as an analytical sensor for a spectralprint (nontargeted) analysis.